IGR J17448-3232 point source: A blazar candidate viewed through the galactic centre? - Curran, Peter; Chaty, S.; Heras, J.; Tomsick, J.; Maccarone, T. (2011)
The error region of the INTEGRAL source, IGRJ17448-3232, contains an X-ray point source at the edge of a ~ 3' radius extended X-ray source. It has been suggested that the extended emission is a young supernovae remnant (SNR) while the point source may be an isolated neutron star, associated with the SNR, that received a kick when the supernova occurred. We identify the infrared counterpart of the X-ray point source, visible from 2.2 µm to 24 µm, and place limits on the flux at longer wavelengths by comparison with radio catalogues. Multi-wavelength spectral modeling shows that the data are consistent with a reddened and absorbed single power law over five orders of magnitude in frequency. This implies non-thermal, possibly synchrotron emission that renders the previous identification of this source as a possible pulsar, and its association to the SNR, unlikely; we instead propose that the emission may be due to a blazar viewed through the plane of the Galaxy.